Identification of the catalytic subunit of brain adenylate cyclase: a calmodulin binding protein of 135 kDa. - Coussen, F (1985)
The partial purification of the eukaryote adenylate cyclase [ATP pyrophosphate-lyase (cyclizing), EC 4.6.1.1] catalytic subunit has been achieved by a procedure based on the calmodulin (CaM) sensitivity of the enzyme. Small amounts of rat brain synaptosomal membranes depleted of CaM were solubilized with Lubrol and subjected to a three-step chromatographic procedure involving gel filtration, a CaM-Sepharose affinity step, and fast protein liquid chromatography. About 20% of the adenylate cyclase activity contained in the membranes was recovered in the final enriched fraction with a specific activity of 200 nmol X mg-1 X min-1. The alpha subunits of the adenylate cyclase stimulatory proteins NS were absent from this final fraction. The addition of CaM, of forskolin, or of preactivated NS-containing fractions to this preparation greatly increased the enzyme activity. A CaM-binding polypeptide of 135,000 Da copurified with the adenylate cyclase activity in each of the three steps. Polyacrylamide gel electrophoresis of the final fraction showed that this polypeptide represented 35% of the total protein. We propose that this polypeptide is likely to be the adenylate cyclase catalytic subunit. This enzyme would represent close to 0.5% of the synaptosomal membrane proteins. Its low turnover number would be due to the absence of the alpha subunits of the NS regulatory proteins and would correspond to the enzymic basal level.